2016
DOI: 10.1063/1.4941091
|View full text |Cite
|
Sign up to set email alerts
|

Accurate molecular dynamics and nuclear quantum effects at low cost by multiple steps in real and imaginary time: Using density functional theory to accelerate wavefunction methods

Abstract: The development and implementation of increasingly accurate methods for electronic structure calculations mean that, for many atomistic simulation problems, treating light nuclei as classical particles is now one of the most serious approximations. Even though recent developments have significantly reduced the overhead for modeling the quantum nature of the nuclei, the cost is still prohibitive when combined with advanced electronic structure methods. Here we present how multiple time step integrators can be c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(78 citation statements)
references
References 50 publications
4
74
0
Order By: Relevance
“…Because NQE are generally larger in H 2 O than in D 2 O hydrogen bonds, the former are weakened most by quantum fluctuations. This leads to the surprising conclusion the static‐electronically weaker hydrogen‐bond in D 2 O becomes stronger when NQE are taken into account, which is consistent with AI‐PIMD simulations of others . This effect is, however, weaker in bulk water than in the isolated water dimer.…”
Section: Discussionsupporting
confidence: 85%
“…Because NQE are generally larger in H 2 O than in D 2 O hydrogen bonds, the former are weakened most by quantum fluctuations. This leads to the surprising conclusion the static‐electronically weaker hydrogen‐bond in D 2 O becomes stronger when NQE are taken into account, which is consistent with AI‐PIMD simulations of others . This effect is, however, weaker in bulk water than in the isolated water dimer.…”
Section: Discussionsupporting
confidence: 85%
“…al. [78]. It boils down to the the use of multiple time steps in real and imaginary time in which one uses a cheap reference potential which captures well the short ranged part of the potential.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to the need to separate the time-scales present in the potential energy, the application of RPC to ab initio PIMD simulations has provided more of a challenge. However, recent work has shown that RPC can be used to dramatically accelerate both DFT(139) and MP2 (197) calculations, while retaining chemical reactivity, by using a reference potential to create a smooth difference force which can then be evaluated on the contracted ring polymer.…”
Section: Ring Polymermentioning
confidence: 99%